The challenges of defining and measuring women's social and economic progress - Austen, Siobhan; Jefferson, Therese; Preston, Alison (Curtin University of Technology, 2000)
We examine six studies which use social indicators to assess women?s status and progress. We then identify the underlying social and economic goals assumed to be relevant to women and analyse the suitability of current social indicators for measuring progress toward these goals. We find that although each of the six studies uses a variety of meaningful indicators, it is relatively easy to identify significant areas of women?s experiences that remain neglected. We suggest that these ?blind spots? may result from two possible and related sources. The first relates to the method in which definitions of women?s progress are constructed. The second reflects poor or limited data collection in some significant areas of relevance to women?s social and economic status.